2013
DOI: 10.1002/jgrc.20120
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional mixture simulations of flow over dynamic rippled beds

Abstract: [1] A three-dimensional mixture theory model for flow and sediment transport in the seafloor boundary layer, SedMix3D, simulated the flow over and the resulting sediment entrainment and evolution of rippled beds. SedMix3D treats the fluid-sediment mixture as a continuum of varying density and viscosity with the concentration of sediment and velocity of the mixture simulated by the Navier-Stokes equations coupled with a sediment flux equation for the mixture. Model validation was performed by comparing simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Using a three‐dimensional mixture model, Penko et al . [] showed that for the present experimental conditions vortices formed and dissipated nonuniformly in the cross‐flow direction due to random fluctuations, yet swirling strength comparisons were generally favorable. Although turbulent intensities measured in this effort are fairly consistent with previous studies (see section 4.1), we anticipate that the effects of three‐dimensionality may influence the Reynolds stress estimates, which accounts for ∼20% of the total RMS stress (section 4.4).…”
Section: Observationsmentioning
confidence: 71%
See 2 more Smart Citations
“…Using a three‐dimensional mixture model, Penko et al . [] showed that for the present experimental conditions vortices formed and dissipated nonuniformly in the cross‐flow direction due to random fluctuations, yet swirling strength comparisons were generally favorable. Although turbulent intensities measured in this effort are fairly consistent with previous studies (see section 4.1), we anticipate that the effects of three‐dimensionality may influence the Reynolds stress estimates, which accounts for ∼20% of the total RMS stress (section 4.4).…”
Section: Observationsmentioning
confidence: 71%
“…A phase lead of 15°, computed with cross‐correlation analysis, is present at the lower 0.7 cm of the water column, consistent with the numerical effort of Penko et al . [], and previous laboratory [ van der Dominic et al ., ], and field [ Foster et al ., ] observations over a flat bed. Figure a shows that in general, u is ∼O(10) times larger than w.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at the Reynolds numbers involved in the experiments, the turbulent structure of the flow and its interaction with the sediment are known to be highly three-dimensional (Ozdemir et al 2010;Penko et al 2013). Of particular importance are the three-dimensional vortical structures which provide the regions of upward directed flow necessary for sediment to travel away from the bed and remain in suspension.…”
Section: Three-dimensional Descriptionmentioning
confidence: 99%
“…Models capable of resolving fine-scale hydrodynamics and sediment transport within the WBBL include ReynoldsAveraged Navier-Stokes (RANS) models (e.g., Winterwerp, 2001;Bakhtyar et al, 2009;Hsu et al, 2009); Large-Eddy Simulation (LES) models (e.g., Zedler and Street, 2001;Chang and Scotti, 2004;Harris and Grilli, 2012); and Direct Numerical Simulation (DNS), which resolves all scales of turbulent flow without the use of a closure model (e.g., Bhaganagar and Hsu, 2009;Ozedmir et al, 2010). Recent advancements have also included capturing the feedback between sediment and fluid within the WBBL, such as utilizing mixture theory within unfiltered Navier-Stokes equations to capture sand ripple dynamics (Penko et al, 2011(Penko et al, , 2013. Models for resolving the motion of cm-sized particles such as SOAs or cobbles have been developed using balance-of-force approaches assuming the particle is driven primarily by the freestream flow, neglecting influences of the WBBL (e.g., Voropayev et al, 1998Voropayev et al, , 2001, but these models do not capture interactions with bed forms.…”
Section: Introductionmentioning
confidence: 98%